Research ethics and the perspective of the principle of autonomy in the professional project and in Social Work research (Práxis Educativa, 2023)
This paper addresses ethics in research from the foundation of the ethical-political project of Social Service that is materialized, among other documents, in the Code of Ethics of Social Workers of 1993. This research was conducted through a literature review, reflections about the experience of the author and discussions about the research projects evaluated by the Ethics Committee in which she works. In this article, it is presented some issues related to the principle of autonomy, a central point in the evaluations of ethics committees, but with a focus on the conception of training in Social Work. The results point to the need to respect the epistemological specificities of the different areas of knowledge in the production of science, at the risk of generating damages to science and the production of knowledge, especially research in Social Work.Keywords: Ethics in research. Social Service. Autonomy.